Web Profile Unit Usaha Universitas Pembangunan Panca Budi - Wisnu Wardhana; Nurul Fadhillah; Putri Khairunnisa; Niko Surya Atmaja (Lembaga Pengembangan Kinerja Dosen, 2023)
Panca Budi Development University has many business units that serve students / I to buy and obtain lectures and food and beverage needs. The UNPAB business unit is located in the middle of the campus. The UNPAB business unit has several businesses including Photo Copy, Home Cafe, Padi Mart and Laziz Canteen. Photo Copy provides learning and teaching equipment, laminating, binding and so on. Café Beranda provides various types of snacks such as soup, french fries. Padi Mart provides minimarket snacks. And the Laziz Canteen provides heavy meals such as fried rice with other side dishes, there is also a water depot. The problem that occurs is that the whereabouts of all UNPAB Business Units are unknown apart from staff, lecturers, students and UNBAP students, so sales do not increase and cause unstable turnover considering that many business unit operational needs must be paid for, this can cause the business unit to not develop. Therefore a way is needed so that the UNPAB Business Unit is better known and known by the wider community. This research makes a web Profile application so that the UNPAB Business Unit can be known by the wider community. The application is made using web programming which consists of two users, namely business unit data managers and the community. Business unit data managers serve as servers and the public serve as users. This application uses data management media, namely the MySQL Database. With the UNPAB Business Unit Web Profile, the UNPAB Business Unit is better known and known by the wider community.